Fontes de informação para acadêmicos do Programa de Pós-Graduação em Agronomia Tropical - Siqueira, Thiago Giordano de Souza (Brasil, 2018)
Presents the databases and scientific journals available within the specific knowledge area. It aims to show scholars where they can possibly find information to solve their information problems for the development of their respective research.